Effect of crocin and quercetin supplementation in cryopreservation medium on post-thaw human sperm quality - Salehi, Ensieh; Shadboorestan, Amir; Mohammadi-Bardbori, Afshin; Mousavi, Abedeh; Kargar-Abargouei, Elias; Sarkoohi, Parisa; Omidi, Mahmoud (Cell and tissue banking, 2024)
Biochemical and physical changes during the cryopreservation process adversely affect sperm function required for fertilization. Recently, many studies have been conducted to find effective pre-freezing treatments to limit these damages. The present study aimed to investigate the effects of pre-freezing treatment with quercetin and crocin, individually or in combination, on sperm parameters after thawing procedure. For this, semen samples from 20 normozoospermic men were collected and then each sample was divided into five equal parts: 1. fresh group 2. frozen–thawed group without addition of antioxidants 3. frozen–thawed group containing 1 mM crocin, 4. frozen–thawed group containing 50 μM quercetin, and 5. frozen–thawed group containing a combination of 1 mM crocin and 50 μM quercetin. Pre-cryopreservation and post-thaw sperm motility, morphology, viability, DNA fragmentation, reactive oxygen species [1] (ROS) levels, and mitochondrial membrane potential [2] (MMP) were investigated. Cryopreservation significantly reduced sperm quality. Both crocin and quercetin individually improved sperm progressive motility, decreased ROS levels, reduced DNA fragmentation, and marginally increased MMP, though crocin seems to be more successful in protecting sperm quality. More interestingly, the combined addition of crocin and quercetin to the sperm-freezing medium did not show positive effects on sperm quality. Crocin and quercetin may play a role in mitigating the cryopreservation-induced injury to sperm.